Personalization vs. Privacy: Balancing Customer Data Use with Ethical Marketing Practices - Rahman, Ahmad Vajri; Dika, Riri Putri; Khairi, Awalul (Equator Journal of Management and Entrepreneurship (EJME), 2024)
This study explores the balance between personalization and privacy in ethical marketing practices, examining how companies can effectively use customer data for personalized marketing without violating privacy rights. As personalization has become a crucial element in enhancing customer experiences, privacy concerns have escalated, driven by the increasing volume of data breaches and stricter privacy regulations such as GDPR and CCPA. Through a qualitative approach, the research gathers insights from key stakeholders, including customers, companies, and regulators, using in-depth interviews and focus group discussions. The findings reveal that while customers value personalization, they are highly concerned about data privacy, emphasizing the need for transparent consent-driven practices. Companies face challenges navigating complex data privacy regulations, but those prioritizing ethical data use, such as Apple with its privacy-centric strategies, are more successful in maintaining customer trust. This study highlights the importance of integrating technologies like data anonymization, encryption, and blockchain to protect customer privacy while enabling effective personalization. However, limitations such as the sample size and scope of the study suggest that further research is needed to explore the long-term effects of privacy regulations on marketing innovation and to offer sector-specific solutions for balancing personalization and privacy. This research provides valuable insights for businesses, regulators, and customers in navigating the evolving landscape of data-driven marketing.